Menurunkan Kejadian Demam Berdarah Dengue dengan Pengetahuan dan Pelaksanaan Pencegahan - Rita Sari; Anifatmawati Anifatmawati (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
Background: DHF is still an endemic problem for people. Prevention and eradication of DHF until now has not been able to free the community from DHF. Objective: This study aims to determine the relationship of knowledge and implementation of DHF prevention with the incidence of DHF in South Pringsewu in the working area of Pringsewu Public Health Center in 2015. Methods: The subjects of this study are the South Pringsewu community of 80 respondents. This research type is analytic survey, using quantitative research methods with cross sectional approach. The sampling technique in this research uses systematic sampling technique. Bivariate analysis using chi-square test with a confidence level of 95%. Results: The results of the study showed that there was a relationship between the level of knowledge and the incidence of DHF with p value 0.012 (p value 0.05) and there was a correlation between the implementation of prevention with DHF incidence with p value 0.002 (p value 0.05). Conclusion: The incidence of DHF is related to the factor of lack of knowledge and the implementation of prevention of DHF endemic emergence